1997
DOI: 10.1073/pnas.94.25.14168
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll precursors are signals of chloroplast origin involved in light induction of nuclear heat-shock genes

Abstract: Coordination between the activities of organelles and the nucleus requires the exchange of signals. Using Chlamydomonas, we provide evidence that plastidderived chlorophyll precursors may replace light in the induction of two nuclear heat-shock genes (HSP70A and HSP70B) and thus qualify as plastidic signal. Mutants defective in the synthesis of Mg-protoporphyrin IX were no longer inducible by light. Feeding of Mg-protoporphyrin IX or its dimethyl ester to wild-type or mutant cells in the dark resulted in induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
208
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(218 citation statements)
references
References 38 publications
7
208
0
2
Order By: Relevance
“…In Chlamydomonas, intermediates in the chlorophyll biosynthetic pathway modulate the accumulation of transcripts of several nuclear chloroplast genes (Johanningmeier and Howell, 1984;Kropat et al, 1997). Arabidopsis mutants that do not react to norflurazoninduced photo-oxidative damage by repression of Lhcb transcription (genomes uncoupled 1 -5: gun1 -5) were affected in genes encoding proteins involved in tetrapyrrole metabolism: the products of GUN2/HY1 and GUN3/HY2 contribute to heme degradation in the ''Fe branch'' of tetrapyrrole biosynthesis (Mochizuki et al, 2001), GUN5 encodes the CHL H subunit of the Mg-chelatase (Mochizuki et al, 2001), and GUN4 binds product and substrate of Mgchelatase, and activates Mg-chelatase (Larkin et al, 2003).…”
Section: Tetrapyrrole Signallingmentioning
confidence: 99%
“…In Chlamydomonas, intermediates in the chlorophyll biosynthetic pathway modulate the accumulation of transcripts of several nuclear chloroplast genes (Johanningmeier and Howell, 1984;Kropat et al, 1997). Arabidopsis mutants that do not react to norflurazoninduced photo-oxidative damage by repression of Lhcb transcription (genomes uncoupled 1 -5: gun1 -5) were affected in genes encoding proteins involved in tetrapyrrole metabolism: the products of GUN2/HY1 and GUN3/HY2 contribute to heme degradation in the ''Fe branch'' of tetrapyrrole biosynthesis (Mochizuki et al, 2001), GUN5 encodes the CHL H subunit of the Mg-chelatase (Mochizuki et al, 2001), and GUN4 binds product and substrate of Mgchelatase, and activates Mg-chelatase (Larkin et al, 2003).…”
Section: Tetrapyrrole Signallingmentioning
confidence: 99%
“…The role of plastids in the control of nuclear gene expression and photomorphogenesis is believed to occur through a plastid signaling pathway. Biochemical and genetic methods have identi®ed two possible components, chlorophyll precursors (Johanningmeier and Howell, 1984;Kropat et al, 1997;Nobuyoshi et al, 2001) and the plastoquinone redox state (Alfonso et al, 2000;Escoubas et al, 1995;Pfanneschmidt et al, 1999). In previous studies (Cao et al, 2000), blocking photosynthesis of wild-type seedlings with 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) caused a decrease in the expression of the ferredoxin gene but had no effect on the subset of light-induced genes whose expression is decreased in cr88 seedlings.…”
Section: Indirect Effect Of Cr88 In Photomorphogenesis and Nitrate Asmentioning
confidence: 99%
“…These observations led to the proposal that communication between plastids and nucleus is mediated through a`plastid signal' (Oelmuller and Briggs, 1990). Genetic and biochemical studies using green algae have identi®ed chlorophyll precursors, tetrapyrroles, and the redox state of chloroplast as possible signals (Escoubas et al, 1995;Johanningmeier, 1988;Johanningmeier and Howell, 1984;Kropat et al, 1997). The isolation of gun mutants in Arabidopsis that are defective in this communication, and the identi®cation of these genes also point towards tetrapyrrole involvement in the`plastid signal' (Nobuyoshi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Plastid-dependent regulation of nuclear genes has been previously described. In Chlamydomonas reinhardtii, the chlorophyll precursors act as intermediates in the light-regulated signaling pathway controlling the transcription rate of the nuclear heat shock genes hsp70a (cytosolic) and hsp70b (chloroplastic; Kropat et al, 1997). Light regulation of Fed-1 (chloroplastic ferredoxin) mRNA abundance in leaves of green plants is posttranscriptionally regulated.…”
Section: Discussionmentioning
confidence: 99%
“…We have, at present, no data for suggesting which is the molecular identity of the chloroplast signal exiting the chloroplast. Previous works have suggested that protoporphyrin IX may act as a possible diffusing compound reaching the cytoplasm through an envelope-localized ABC transporter (Kropat et al, 1997;Moller et al, 2001). However, we did not observe changes in protoporphyrin IX levels in barley mutants impaired in chloroplast-dependent cor gene expression.…”
Section: Discussionmentioning
confidence: 99%